Flanksnitt som alternativ till linea-albasnitt vid ovariohysterektomi av tik - Hansson, Marie (2005)
In Sweden, the most common way to castrate a bitch is by midline approach. In this study, flank and midline approaches are compared in order to evaluate incision by the flank as an alternative technique for ovariohysterectomy in the bitch. The study was performed on straydogs in the central part of Thailand under field conditions. 32 bitches were included in the study. The castration technique was by flank and midline approach, alternating with every other bitch. Time needed for the surgery, amount of suture material used and peri as well as post surgery complications were estimated. The study showed that the time used for surgery was equivalent for the two different techniques. The midline approach though, had a larger variation in time. The amount of suture material used was almost the same for both techniques. Dogs who were castrated by the midline approach had more complications with respect to bleedings from the ligatures during surgery. However, tissue bleeding when passing the abdominal wall was found to be less in this group. Post surgery complications as inflammation and infection were similar for the two techniques. The results of this study show that the flank approach can be a proper alternative to the midline approach.